Hydrophobic thiol coatings to facilitate a triphasic interface for carbon dioxide reduction to ethylene at gas diffusion electrodes. (15th April 2021) - Perry, Samuel C.; Mavrikis, Sotirios; Wegener, Moritz; Nazarovs, Pāvels; Wang, Ling; Ponce de León, Carlos
Abstract : In this work, we report the use of hydrophobic 1-octadecanethiol coatings at copper coated gas diffusion electrodes to enhance the production of ethylene. Abstract : The electrochemical reduction of CO2 continues to see significant interest as a viable means of both producing important chemical materials and lowering carbon emissions. The primary challenge to making this process economically viable is the design of catalyst, electrode and reactor components that can selectively produce just one of the many possible CO2 reduction products. In this work, we report the use of hydrophobic 1-octadecanethiol coatings at copper coated gas diffusion electrodes to enhance the production of ethylene. This thiol coating gives a substantial increase in the production of ethylene at low current densities as well as a change in the rate determining step, as indicated by the substantial reduction in the Tafel slope. The observed changes to the CO2 reduction reaction indicate that the thiol layer provides a triphasic interface within the gas diffusion electrode catalyst layer.